2014
DOI: 10.2147/ijn.s61103
|View full text |Cite
|
Sign up to set email alerts
|

Efficient gene delivery system mediated by cis-aconitate-modified chitosan-g-stearic acid micelles

Abstract: Cis-aconitate-modified chitosan-g-stearic acid (CA-CSO-SA) micelles were synthesized in this study to improve the gene transfection efficiency of chitosan-g-stearic acid (CSO-SA). The CA-CSO-SA micelles had a similar size, critical micelle concentration, and morphology, but their zeta potential and cytotoxicity were reduced compared with CSO-SA micelles. After modification with cis-aconitate, the CA-CSO-SA micelles could also compact plasmid DNA (pDNA) to form nanocomplexes. However, the DNA binding ability of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…The first section conveys information on probably the best-known and most intensively studied biosimilar NMs applied in biotechnology and medicine such as liposomes, chitosan, and poly(lactic-co-glycolic acid) (PLGA) nanoparticles. These biocompatible and biodegradable NMs represent wide potential use in delivering a large variety of drugs and therapeutics including small molecules, herbal medicines, genes, proteins, miRNAs, and oligonucleotides ([ 30 , 31 ] and references cited; [ 9 , 14 , 22 , 25 , 32 34 ]). The focus of the second section is on the possibility to conclude on trait-nanotoxicity relationships.…”
Section: Emerging Consensusmentioning
confidence: 99%
See 1 more Smart Citation
“…The first section conveys information on probably the best-known and most intensively studied biosimilar NMs applied in biotechnology and medicine such as liposomes, chitosan, and poly(lactic-co-glycolic acid) (PLGA) nanoparticles. These biocompatible and biodegradable NMs represent wide potential use in delivering a large variety of drugs and therapeutics including small molecules, herbal medicines, genes, proteins, miRNAs, and oligonucleotides ([ 30 , 31 ] and references cited; [ 9 , 14 , 22 , 25 , 32 34 ]). The focus of the second section is on the possibility to conclude on trait-nanotoxicity relationships.…”
Section: Emerging Consensusmentioning
confidence: 99%
“…Numerous studies are concerned about the more specific and more efficient delivery of therapeutics by applying specific combinations of biocompatible and biodegradable NMs ([ 33 ] and reference cited). For recent examples we may conjecture more efficient transfection of nucleic acid-based therapeutics based on the modification of chitosan combined g-stearic acid micelles by cis-aconitate [ 34 ] or more effective targeted delivery of osthole by N-succinyl-chitosan nanoparticles coupled with low-density lipoprotein [ 22 ].…”
Section: Furthering Evidence On Biocompatible and Biodegradable Pomentioning
confidence: 99%
“…The incorporation of bovine serum albumin (isoelectric point value = 4.7) into CS/pDNA accelerated vector unpacking, thereby showing higher transfection efficiency than CS/pDNA counterparts . Our previous studies have also demonstrated that the addition of acids or negatively charged groups is beneficial to the gene transfection of CS/pDNA complexes. …”
Section: Introductionmentioning
confidence: 99%
“…14 Our previous studies have also demonstrated that the addition of acids or negatively charged groups is beneficial to the gene transfection of CS/pDNA complexes. [14][15][16] Cationic-based delivery systems can be eliminated by the reticuloendothelial system (RES). 5 Therefore, polymers with covalently bound hydrophilic materials, such as poly(ethylene glycol) (PEG), were developed to prevent rapid clearance.…”
Section: Introductionmentioning
confidence: 99%